การพัฒนาตัวบ่งชี้คุณธรรมจริยธรรมของครูพลศึกษา - อัจฉราลักษณ์ วิเศษ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purposes of this research was to develop moral virtues indicators of physical education teacher by synthesizing moral virtues indicators of physical education teacher and testing the validities of the developed indicators. In testing for content validity, the indicators were screened and examined by ten physical education experts. A Confirmatory Factor Analysis with empirical data was utilized to test for construct validity. The sample of this research were 666 physical education teachers from all parts of Thailand derived from multi-level random sampling method. The research instrument was a self-assessment report on conduct of oneself according to the moral virtues indicators of physical education teacher. The basic data was analized by using descriptive statistics and reported as Means, S.D., C.V., Skewness, and Kurtosis. In addition, the Confirmatory Factor was analyzed by utilizing the LISREL 8.80 program.The results revealed that the moral virtues indicators of physical education teacher comprised of 10 components namely; Sportsmanship, Good Model, Responsibility, Honesty, Kindness, Justice, Sacrifice, Passion and Faith in the Profession, Gratefulness, and Discipline. The Confirmatory Factor Analysis found that the developed moral virtues indicators were fairy congruent with the compared empirical data as shown by a chi– square value of 4628.24, probability (p) of 0.000 level, degrees of freedom (df) of 1731, chi- relative Square (2/df) of 2.67, Goodness of Fit Index (GFI) of 0.81, Adjusted Goodness of Fit Index (AGFI) of 0.80, Comparative Fit Index(CFI) of 0.99, Standardized Root Mean Squares Residual (SRMR) of 0.045, and Mean Squares Error of Approximation (RMSEA) of 0.050. The standardized loading values of all elements varied from 0.77 to 0.93. In conclusion, the ten moral virtues were appropriate moral virtues indicators for physical education teacher with validity in indication. Sportsmanship was the most significant moral virtues in indicating moral virtues of physical education teacher.